2020
DOI: 10.3389/fmicb.2020.01850
|View full text |Cite
|
Sign up to set email alerts
|

Azole-Resistant Aspergillus fumigatus Among Danish Cystic Fibrosis Patients: Increasing Prevalence and Dominance of TR34/L98H

Abstract: Azole-resistant (azole-R) Aspergillus is an increasing challenge worldwide. Patients with cystic fibrosis (CF) are at risk of Aspergillus colonization and disease due to a favorable lung environment for microorganisms. We performed a nationwide study in 2018 of azole-non-susceptible Aspergillus in CF patients and compared with data from two prior studies. All airway samples with mold isolates from patients monitored at the two CF centers in Denmark (RH, Jan-Sept and AUH, Jan-Jun) were included. Classical speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…In Denmark, Risum et al. recently reported the occurrence of AR Af strains in 7.3% (10/137) CF patients ( Risum et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Denmark, Risum et al. recently reported the occurrence of AR Af strains in 7.3% (10/137) CF patients ( Risum et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A global rate of resistance of A. fumigatus is however a metric with little significance, especially if we do not take into account variability between patients and drugs. During CF, particularly-high rates of AR Af have been reported ( Stevens et al., 2003 ; Mortensen et al., 2011 ; Burgel et al., 2012 ; Morio et al., 2012 ; Meis et al., 2016 ; Prigitano et al., 2017 ; Risum et al., 2020 ; Wiederhold and Verweij, 2020 ) while azoles are recommended in the guidelines for the management of allergic bronchopulmonary aspergillosis (ABPA) ( Stevens et al., 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory observations support the recent report of recovery of genetically closely related TR 34 3 /L98H and TR 34 /L98H isolates from a cystic fibrosis patient. The patient had been treated with VOR and POS (MC Arendrup, personal communication), which could have selected TR 34 3 /L98H harboring A. fumigatus strains in the lung [ 9 ]. However, the TR 34 /L98H patient isolate was recovered after the isolates harboring TR 34 3 /L98H and no ancestral isolate was available [ 9 ], therefore it is unclear whether the TR 34 3 -variant evolved in the host under VOR and POS selection from a TR 34 or vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…Recently a TR 34 3 /L98H variant was recovered from a cystic fibrosis patient who also harbored a TR 34 /L98H isolate. Microsatellite typing showed that the TR 34 3 /L98H and TR 34 /L98H shared eight of nine markers, which supports possible in vivo acquisition of an additional TR [ 9 ]. Apparently not the resistance selection route, but other factors such as chemical characteristics of the azole, the reproduction mode the fungus goes through and azole stress duration might determine which resistance mutation is selected for [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation